Informatic Video Increased The Number of Acceptors in Post Placental Insertion of Intrauterine Device (IUD): Video Informasi Meningkatkan Jumlah Akseptor Alat Kontrasepsi Dalam Rahim (AKDR) Pascaplasenta - Gladys Susanty; Eddy Tiro; Fatmawaty Madya; Isharyah Sunarno; Mardiah Tahir; Telly Tessy (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: To find out the role of informatic video in obtaining consent for post placental insertion of Intrauterine Device (IUD) Methods: This was a prospective randomized controlled trial. The informatic video was given to the study group compared by the level of acceptance of the respondents in the control group that was given conventional methods. This research was carried out in Pertiwi, Fatimah, and Khadijah I Mother and Child Hospital Makassar. The data were analyzed by chi-square test with significant level p<0.05. Results: There was a significant correlation between informatic video groups to the consent (p=0.026) and the insertion (p=0.034) of post placental IUCD. The informatic video had the effects to increased the number of acceptors post placental IUCD with the value of significance as 0.018, therefore if the informatic video was increased, then the consent of insertion IUCD was also increased. Conclusions: Informatic video had the effects of increased the number of acceptors post placental IUCD. Keywords: informatic video, postplacental insertion of Intra-Uterine Contraceptive Device (IUCD) Abstrak Tujuan: Mengetahui hubungan antara video informasi dalam pengambilan persetujuan tindakan medis pada pemasangan AKDR pasca plasenta. Metode: Penelitian ini merupakan penelitian kohort dengan uji acak terkontrol prospektif. Jenis penelitian ini adalah penelitian uji kohort dimana peneliti memberikan tayangan video informasi pada kelompok penelitian serta membandingkan tingkat penerimaan pasien terhadap AKDR dengan kelompok kontrol. Penelitian ini dilaksanakan di Rumah Sakit Khusus Daerah Ibu dan Anak Pertiwi, Rumah Sakit Khusus Daerah Ibu dan Anak Fatimah, Rumah Sakit Ibu dan Anak Khadijah I Makassar. Data dianalisis dengan uji chi-square dengan kemaknaan p<0,05. Hasil: Terdapat hubungan yang bermakna antara pemberian video informasi terhadap persetujuan (p=0,026) dan pemasangan (p=0,034) AKDR pascaplasenta. Video informasi memiliki pengaruh dalam meningkatkan jumlah akseptor AKDR pascaplasenta dengan nilai signifikansi sebesar 0,018, sehingga jika bantuan video informasi meningkat maka keputusan dalam pemasangan AKDR juga meningkat. Kesimpulan: Video informasi memiliki pengaruh dalam meningkatkan jumlah akseptor AKDR pasca plasenta. Kata kunci: AKDR pascaplasenta, video informasi